KETIDAKSEIMBANGAN KEDUDUKAN PARA PIHAK DALAM PERJANJIAN KREDIT PERBANKAN (STUDI PADA BANK MESTIKA DHARMA MEDAN) - Siti Dyara Aisha (UNIVERSITAS PEMBANGUNAN PANCA BUDI, 2021)
In the credit agreement made under the hands there is an imbalance that occurs between the parties. The imbalance that occurs due to the standard clauses contained in the underhand agreement and this can be burdensome for one of the parties. The imbalance that occurs is considered to have violated the principle of freedom of contract, the Consumer Protection Law, and the Financial Services Authority Regulation, as well as the absence of bargaining conditions. This research was conducted on credit agreements at Bank Mestika Dharma Medan Branch.The purpose of the study is to analyze the imbalance of credit agreements made underhand, to analyze the problems faced by Bank Mestika Dharma Medan Branch regarding the use of private credit agreements, and to analyze legal protection efforts against the parties in private credit agreements. To answer this problem, normative juridical research is used by examining the juridical construction of under-handed agreement arrangements. The data are collected through library research and field research, that are obtained through document studies and interview guidelines.It is recommended to provide balanced rights and obligations between debtors and creditors, because in private credit agreements they prioritize the interests of the bank rather than the debtor. It is necessary to refine the policy on private credit agreements, so that there is a balance between the parties.